1997
DOI: 10.1002/ceat.270200405
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Exchange membrane processes for clean industrial chemistry

Abstract: New uses of artificial selective membranes, particularly ion‐exchange membranes, improve on traditional methods of treating liquid mixtures before, during or after chemical or biochemical reactions. With the correct choice of ion‐exchange membrane in a membrane reactor, reactions can be performed in such a way that the main product is not contaminated by undesired byproducts. Recent examples, mainly in organic chemistry, are given for eight typical ion‐exchange membrane reactors: electrodialysis (ED), electrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Aiming at presenting ED membrane phenomena-based processes, some technologies were not detailed: membrane-free electrodeionization [ 123 ], electrostatic shielding electrodeionization [ 124 ] used for metal ion removal, microbial desalination cell for wastewater treatment, pure water and energy production [ 125 ] and redox flow battery for energy production [ 126 ]. Furthermore, the lack of recent developments led us to not detailed electro-ion injection-extraction (EIIE), electro-ion substitution (EIS) and electrometathesis (EMT) [ 127 , 128 , 129 ], mostly used for the recovery of organic acids.…”
Section: Recent Technological Developments Based On Ed Membrane Phmentioning
confidence: 99%
“…Aiming at presenting ED membrane phenomena-based processes, some technologies were not detailed: membrane-free electrodeionization [ 123 ], electrostatic shielding electrodeionization [ 124 ] used for metal ion removal, microbial desalination cell for wastewater treatment, pure water and energy production [ 125 ] and redox flow battery for energy production [ 126 ]. Furthermore, the lack of recent developments led us to not detailed electro-ion injection-extraction (EIIE), electro-ion substitution (EIS) and electrometathesis (EMT) [ 127 , 128 , 129 ], mostly used for the recovery of organic acids.…”
Section: Recent Technological Developments Based On Ed Membrane Phmentioning
confidence: 99%
“…It is well known that electrochemical properties of the membranes have a significant effect on RED performance based on various commercially available membranes being tested and evaluated within a RED stack for generating power [4,7,[15][16][17][18]. Lacey concluded that RED-specific membrane should have properties of low electrical resistance, high selectivity, long service life, acceptable strength, dimensional stability, and low cost [19]. Vermaas et al demonstrated that power density of RED system could be improved through reducing membrane resistance and intermembrane distances [7].…”
Section: Introductionmentioning
confidence: 99%
“…Electrodialysis (ED) is a type of technology which arranges ion‐exchange membranes alternately in a direct current field 1–23. As shown in Figure 1a, there are at least five elements complementary for ED applications4: (1) direct current supply, which proves effective to reinforce ion migration; (2) electrodes, where the oxidation/reduction reactions occur to realize the transformation from ionic conduction to electron conduction and thus provide the original driving force for ion migration; (3) ion exchange membranes, the key components which permit the transport of counter ions and block the passage of co‐ions; (4) solvents, which make a continuum for ion transport by filling the space between electrodes and membranes; (5) electrolytes, the current carriers between cathode and anode.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1a, there are at least five elements complementary for ED applications4: (1) direct current supply, which proves effective to reinforce ion migration; (2) electrodes, where the oxidation/reduction reactions occur to realize the transformation from ionic conduction to electron conduction and thus provide the original driving force for ion migration; (3) ion exchange membranes, the key components which permit the transport of counter ions and block the passage of co‐ions; (4) solvents, which make a continuum for ion transport by filling the space between electrodes and membranes; (5) electrolytes, the current carriers between cathode and anode. Owning to its distinguished functions, ED has been widely used to demineralize, concentrate and/or convert salt‐containing solutions 4–9. Notably, a recent invention explored a new and broad space for ED development: bipolar membrane.…”
Section: Introductionmentioning
confidence: 99%